Aetiology, incidence and morphology of the C‐shaped root canal system and its impact on clinical endodontics. (31st March 2014) - Kato, A.; Ziegler, A.; Higuchi, N.; Nakata, K.; Nakamura, H.; Ohno, N.
Abstract The C‐shaped root canal constitutes an unusual root morphology that can be found primarily in mandibular second permanent molars. Due to the complexity of their structure, C‐shaped root canal systems may complicate endodontic interventions. A thorough understanding of root canal morphology is therefore imperative for proper diagnosis and successful treatment. This review aims to summarize current knowledge regarding C‐shaped roots and root canals, from basic morphology to advanced endodontic procedures. To this end, a systematic search was conducted using the MEDLINE, BIOSIS, Cochrane Library, EMBASE, Google Scholar, Web of Science, PLoS and BioMed Central databases, and many rarely cited articles were included. Furthermore, four interactive 3D models of extracted teeth are introduced that will allow for a better understanding of the complex C‐shaped root canal morphology. In addition, the present publication includes an embedded best‐practice video showing an exemplary root canal procedure on a tooth with a pronounced C‐shaped root canal. The survey of this unusual structure concludes with a number of suggestions concerning future research efforts.